An extension of the Hill–Mandel principle for transient heat conduction in heterogeneous media with heat generation incorporating finite RVE thermal inertia effects. (25th January 2017) - Ramos, Gustavo Roberto; dos Santos, Tiago; Rossi, Rodrigo
Summary: In this work, we propose a homogenization formulation to model transient heat conduction in heterogeneous media that takes into account thermal inertia contributions, which arise from a finite description of the microscale. Rewriting the variational form of the transient heat conduction problem and making use of key assumptions, we arrive at a mathematical formulation that suggests an extension of the Hill–Mandel principle when considering non‐null heat flux divergence in the representative volume element (RVE). Along the manuscript, we highlight that the main results of the proposed formulation are in agreement with recent advances in the field of computational homogenization applied to transient mechanical and heat flow problems. The proposed extension of the Hill–Mandel principle contributes to the understanding of the microscale thermal inertia effects incorporation into the multiscale framework. We also present the calculations needed for implementing the model and numerical results, which give support to the theoretical model developed. The numerical results highlight the importance of considering full transient aspects when dealing with multiscale heat conduction in heterogeneous media which are subjected to high thermal gradients. Copyright © 2016 John Wiley & Sons, Ltd.